SAUSSURE’S ANALYSIS OF SIGNS IN COFFEE SACHET PACKAGING PRODUCED BY PT. SANTOS JAYA ABADI - Septi Rahma Putri Maulida; Tissa Fadhia Alawiya; Zenobia, Zenobia (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This research analyzes the signs found in PT. Santos Jaya Abadi which the signs represent the meaning. It applies a descriptive qualitative approach as the writers analyze the image, word, and visual as signifiers and their meaning as signified. The writers use Sassaure’s concept of the semiotic which are the signifier and signified. It utilizes 30 data of signs from PT. Santos Jaya Abadi. The result of the research is visual images, words, colors, and phrases representing the signifier and the signified.